Orosomucoid 1 is a Potential Prognostic Biomarker for Uterine Sarcoma - Dan Yuan MS; Yue Huang MS; Ying Cai MS; Chi Zhang MS; Jin-Jing Wang MD; Jian-Guo Zhou MD (Technology in Cancer Research & Treatment)
Introduction Uterine sarcoma (US) is a rare tumor characterized by high aggressiveness, a tendency for recurrence and distant metastasis, and an extremely poor prognosis. In this study, we evaluated the expression of Orosomucoid 1 (ORM1) in different subtypes of US and the relationship between survival rates and clinicopathological features. Method A retrospective study was conducted on 50 cases diagnosed with US in our hospital from 2011 to 2023. Immunohistochemistry (IHC) was used to detect the expression levels of ORM1 in different subtypes of US.The chi-square test and Kaplan-Meier survival analysis were used to analyze the relationship between ORM1 expression and clinical parameters as well as prognosis. Cox analysis was employed to evaluate the relationships between prognosis and clinical parameters in US. Result Compared to normal proliferative endometrial tissue (NPE), the expression of ORM1 was downregulated in low-grade endometrial stromal sarcoma (LG-ESS), high-grade endometrial stromal sarcoma (HG-ESS), and undifferentiated uterine sarcoma (UUS) (P < .001,P < .001,and P < .001, respectively). Compared to normal uterine smooth muscle tissue (UNSM), the expression of ORM1 was upregulated in leiomyosarcoma (LMS) (P = .006). High ORM1 expression levels in US patients were associated with poor overall survival (OS) and progression-free survival (PFS) (P = .027 and P = .005, respectively). Multivariate COX analysis revealed that tumor stage and ORM1 expression are independent prognostic factors for US patients. Conclusion ORM1 is expressed at low levels in ESS and at high levels in LMS. ORM1 potentially serve as a novel biomarker for the diagnosis, classification, and prognosis of US.